2016
DOI: 10.1002/bmc.3867
|View full text |Cite
|
Sign up to set email alerts
|

Chemical identification and quality evaluation of Lycopus lucidus Turcz by UHPLC‐Q‐TOF‐MS and HPLC‐MS/MS and hierarchical clustering analysis

Abstract: Lycopus lucidus Turcz has been used as a traditional phytomedicine for menstrual disorder, amenorrhea, menstrual cramps, inflammation and cardiovascular diseases. However, there is not enough information about identification and quantification for the chemical constituents of L. lucidus Turcz. In this work, a simple, rapid and sensitive UHPLC-Q-TOF-MS method was developed for characterization and identification of the phytochemical compositions in L. lucidus Turcz in negative ion mode. A total of 37 compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Ultra-performance liquid chromatography with quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS) has been used in systems analysis of complicated metabolome [ 24 , 28 , 29 ]. A total of 37 compounds in Lycopus lucidus Turcz, including 15 phenolic acids, 12 flavonoids, three triterpenoids and seven organic acids were tentatively characterized and identified by means of the UHPLC-Q-TOF-MS method [ 30 ]. In the same way, 42 polymethoxylated flavonoids, including 33 flavones and nine flavanones, were distinguished in Citrus reticulata and Citrus sinensis [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-performance liquid chromatography with quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS) has been used in systems analysis of complicated metabolome [ 24 , 28 , 29 ]. A total of 37 compounds in Lycopus lucidus Turcz, including 15 phenolic acids, 12 flavonoids, three triterpenoids and seven organic acids were tentatively characterized and identified by means of the UHPLC-Q-TOF-MS method [ 30 ]. In the same way, 42 polymethoxylated flavonoids, including 33 flavones and nine flavanones, were distinguished in Citrus reticulata and Citrus sinensis [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 37 compounds in Lycopus lucidus Turcz, including 15 phenolic acids, 12 flavonoids, three triterpenoids and seven organic acids were tentatively characterized and identified by means of the UHPLC-Q-TOF-MS method [ 30 ]. In the same way, 42 polymethoxylated flavonoids, including 33 flavones and nine flavanones, were distinguished in Citrus reticulata and Citrus sinensis [ 30 , 31 ]. This method was previously applied in Acanthopanax senticosus plants for the simultaneous determination of five major bioactive constituents (eleutheroside B, chlorogenic acid, caffeic acid, eleutheroside E and isofraxidin) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the chemical constituents identified or tentatively characterized in LZHC were mainly triterpenoids and flavonoids, and triterpenoids accounted for the majority. Phenolic acids such as protocatechuic acid, chlorogenic acid, and caffeic acid have significant anti-inflammatory, anti-oxidant, and anti-viral activities [32][33][34] . Likewise, flavonoids including liquiritin, liquiritigenin, and licochalcone A have anti-inflammatory, immunomodulatory, anti-tumor, and anti-bacterial effects [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, we find the species Lycopus europaeus L. and Lycopus exaltatus L.f. The leaves are rich in flavonoids, coumarins, terpenoids, and tannins [ 129 ], and they have use in treating edema, wound healing, T2DM, and pain, especially in traditional Chinese medicine. L. lucidus has been suggested to play a protective role against obesity, NAFLD, and metabolic diseases.…”
Section: Lamiaceae: Bioactive Propertiesmentioning
confidence: 99%